The Influence of Organizational Culture and Career Development Opportunities on the Job Satisfaction of dr. Tjitrowardojo Class B Purworejo - Amilia Tiarani; Ratri Wahyuningtyas (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The existence of Human Resources (HR) is very important in achieving organizational goals, so good HR management, including paying attention to job satisfaction, is crucial. At dr. Tjitrowardojo Class B Purworejo, job satisfaction will be created by implementing a good organizational culture and adequate career development opportunities. This research aims to determine the influence of organizational culture and career development opportunities on employee job satisfaction at the RSUD. The method used is quantitative with data collection techniques through questionnaires filled out by 167 civil servant employees. The sampling technique used is probability sampling with simple random sampling, and data analysis using SEM-PLS. The research results show that organizational culture and career development opportunities have a positive and significant influence on employee job satisfaction. The author suggests that hospitals continue to pay attention to employee job satisfaction by optimizing the application of organizational cultural values ​​and career development through transparency of employee points, dissemination of career information, and ease of career advancement systems.